2004
DOI: 10.1289/ehp.7187
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Asthma and Allergic Symptoms in Children and Phthalates in House Dust: A Nested Case–Control Study

Abstract: Global phthalate ester production has increased from very low levels at the end of World War II to approximately 3.5 million metric tons/year. The aim of the present study was to investigate potential associations between persistent allergic symptoms in children, which have increased markedly in developed countries over the past three decades, and the concentration of phthalates in dust collected from their homes. This investigation is a case–control study nested within a cohort of 10,852 children. From the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
505
6
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 750 publications
(535 citation statements)
references
References 36 publications
13
505
6
11
Order By: Relevance
“…In seven out of 9 cities the average TVOC level was higher than the Chinese Indoor Air Quality Standard (GB/T 18883-2002) [25] of 0.6 mg/m 3 as an 8-hour average. Finally, modern chemicals including phthalates [12], and glycol ethers [13] emitted by indoor decorations and furniture have shown a strong association with asthma and allergies. In this study, 28.7% of families reported new decoration before children's birth and 31.6% new furniture, with more than 60% (64.6%) of children living in the current place since children's birth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In seven out of 9 cities the average TVOC level was higher than the Chinese Indoor Air Quality Standard (GB/T 18883-2002) [25] of 0.6 mg/m 3 as an 8-hour average. Finally, modern chemicals including phthalates [12], and glycol ethers [13] emitted by indoor decorations and furniture have shown a strong association with asthma and allergies. In this study, 28.7% of families reported new decoration before children's birth and 31.6% new furniture, with more than 60% (64.6%) of children living in the current place since children's birth.…”
Section: Resultsmentioning
confidence: 99%
“…Prenatal exposure and early life factors have been less thoroughly studied [6]. Till now, studies have reported that prenatal exposure to tobacco smoke [7,8], presence of home mold odor [9], early life presence of particle-board furniture [10], pollen or spores [11], and new chemicals [12,13] were associated with respiratory symptoms, including asthma and allergic rhinitis, in children later in life.…”
mentioning
confidence: 99%
“…Sources of phthalate exposure include the workplace, diet, off-the-job activities, personal care products, and other home or environmental sources. Phthalates have been evaluated as possible reproductive and developmental toxicants in animals and humans (Hauser and Calafat, 2005;Latini, 2005;Heudorf et al, 2007;Matsumoto et al, 2008) and may also have a function in respiratory disease (Bornehag et al, 2004;Hoppin et al, 2004;Jaakkola and Knight, 2008;Kolarik et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Median house dust concentrations of BBzP were higher in the bedrooms of cases than controls. The risk of allergic rhinitis and eczema was related to the house dust BBzP concentrations, whereas the risk of asthma was related to concentration of DEHP (Bornehag et al 2004). Jaakkola and colleagues (2006) conducted a population-based incident casecontrol study to assess the relations between different types of interior surface materials and recent renovations at home and at work and the risk of asthma in adults.…”
Section: Respiratory Healthmentioning
confidence: 99%